A modernização do litoral norte do Espírito Santo: do processo de “civilização dos índios” ao reconhecimento das populações tradicionais; da mobilização à crise do trabalho - Martini, Evandro Arruda de (2023)
Unlike studies that consider a region, territory or population as isolated, this research seeks to highlight the mediations between a general process of global modernization and the particularities of the modernization of Brazil and the northern coast of Espírito Santo state, inserted in the expanded reproduction of capitalist relations. Concepts and categories such as “sertão”, “virgin land”, “frontier”, “pioneer”, “work” and “commodity” are investigated in relation with the period in which they are used: the concepts change as the processes take place. The mediations of traditional populations in the northern coast of Espírito Santo with the external society are studied since the 19th century: we observe a process that had as its logical goal their integration into the “mass of the civilized population” as workforce, at the same time when their territories were expropriated, as land became autonomous as a commodity. This integration did not happen exactly as planned, but the projects did move processes in reality. In the twentieth century, there are many modernizing projects and actions concerning this northern coast of Espírito Santo, which, for a long time, was considered a “decadent” region with “obsolete” social relations. Planning is consolidated through universities and other developmental institutions. We seek to explain and criticize the theoretical foundations of geography and other sciences that planned this modernization in rational terms in the 20th century. In the 1970s and 1980s, some territories on the north coast underwent a more accelerated modernization with the eucalyptus export complex and other “regional development” enterprises. At the same time, in certain contexts, external threats intensify the struggles of traditional populations. More recently, the paradigm shift from the processes of colonization of “virgin lands” and “civilizing the indigenous” to the recognition of the rights of indigenous peoples, quilombolas and other traditional populations summarizes the changes between the long process of modernization led by a planning State – the latter also in the process of formation – and a more recent period characterized by a crisis-managing State. In this more recent moment, we analyze the conflicts and controversies about large port projects designed and/or implemented on the north coast, given the supposed vocation of Espírito Santo for ports and exportation. Large ports justify themselves socially by generating expectations of job creation, but actually these ports mobilize increasingly fewer local people as workers.